A structural reassessment of the Late Pleistocene femur from Maludong, southwestern China. Issue 4 (14th June 2022) - Wei, Pianpian; Ma, Shiwu; Carlson, Kristian J.; Ji, Xueping; Zhang, Quanchao; Liu, Wu; Jin, Li
Abstract: Objective: The Late Pleistocene partial right femur from Maludong in southwestern China has been attributed characteristics of early Homo, especially from the Early Pleistocene, putatively representing a late surviving archaic population in the region. Assessment of additional traits is warranted given newly described postcrania from the Late Pleistocene of southwestern China and characterized by relatively modern features. Materials and methods: We used micro computed tomography (μCT) to extract and evaluate cross‐sectional diaphyseal structure. New predictions of Maludong femoral length were generated from a regression analysis of Holocene modern humans. Robusticity and shape at multiple, standard diaphyseal regions of interest (ROI) were compared to those of Pleistocene and Holocene humans from East Asia and beyond. Results: Standardized torsional rigidities at mid‐proximal and subtrochanteric Maludong ROIs fell within ranges of variation exhibited by multiple comparative groups, and closest to medians of Early and Middle Upper Paleolithic modern humans (E/MUP). For I x / I y diaphyseal ratios, Maludong was higher than comparative groups at both ROIs, falling closest to the upper end of the E/MUP range. For I max / I min shape ratios, Maludong fell well above group medians at the mid‐proximal ROI and nearest E/MUP and Middle Pleistocene group medians at the subtrochanteric ROI. Discussion and conclusions: In diaphyseal robusticity and rigidity ratios, Maludong fits within variation exhibited by other Late Pleistocene modern humans. While we did not re‐analyze external features described as archaic‐like, internal structure of the Maludong femur contradicts this characterization and instead supports expanding intrapopulation variability expressed by Late Pleistocene modern humans in East Asia.